Penerapan Edukasi Metode Audiovisual terhadap Pengetahuan tentang Anemia pada Ibu Hamil - Fauziah, Ade Fitri; Simamora, Elfrida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the application of audiovisual education methods to improve knowledge of anemia in pregnant women. The method in this study used a pre-experiment design with a one-group pretest-posttest design with a sample size of 34 pregnant women. The results obtained using the t-dependent test showed a p-value of 0.000 <0.005, so H0 was rejected and Ha was accepted, the average (mean) between knowledge of anemia pre-test with a mean result of 53.48 and post-test with a mean result of 94.024. The conclusion is that there is a difference in the average (mean) between before and after using audiovisual education methods on knowledge of anemia in pregnant women. Keywords: Anemia, Audiovisual, Education, Pregnant Women, Knowledge